Determination of hepatitis B and hepatitis C seroprevalence in pregnant women in the Kastamonu region, Turkey - Tüfekci, Enis Fuat; Çalışır, Büşra; Yaşar Duman, Melike; Kılınç, Çetin (MediHealth Academy, 2023)
Aims: Hepatitis B virus (HBV) and hepatitis C virus (HCV) infections during pregnancy have a risk of transmission to the newborn. Therefore, pregnant women are routinely screened for HBV and HCV in many countries. This study aimed to reveal the seroprevalence of HBsAg, anti-HBs, and anti-HCV in pregnant women in the Kastamonu region and to compare the obtained data with the results of studies conducted in Turkey. Methods: Pregnant women who applied to Kastamonu Training and Research Hospital Microbiology laboratory between January 2022 and January 2023 for HBsAg, anti-HBs, and anti-HCV tests were included in this study. The pregnant women were separated into two groups ?24 and >24 age groups. The tests were performed using the chemiluminescence microparticle immune assay method on the Abbott Architect i2000SR instrument, and the results were evaluated per the manufacturer’s instructions. Results: HBsAg, anti-HBs, and anti-HCV positivity were 0.5% (n=9/1712), 51.1% (n=874/1712), and 0.1% (n=2/1713), respectively. While there was no significant difference between age groups for HBsAg positivity (p>0.05), anti-HBs positivity was found to be significantly higher in the ?24 age group than in the >24 age group (p=0.002). Conclusion: The results showed that HBsAg and anti-HCV positivity was lower than in most studies conducted in recent years in Turkey, and anti-HBs positivity was higher than in most studies. It is essential to continue routine HBV and HCV screening in pregnant women’s first follow-up and encourage anti-HBs-negative individuals to be vaccinated against HBV.
Keywords: 3. Good health